Вы находитесь на странице: 1из 41

.

.
. .
2011


1
2
3
4
5
6
7
8
9

. . . . . . . . . . . . . . .
. . . . . . . . . . . .
. . . . . . . . . . . . . . . . . .
. . . . . . . . . . . . . . .
.
. . . . . .
. . . . . . . . . . .
. . . . . . . . . . . . .
- . . . . .

.
.
.
.
.
.
.
.
.

.
.
.
.
.
.
.
.
.

.
.
.
.
.
.
.
.
.

.
.
.
.
.
.
.
.
.

.
.
.
.
.
.
.
.
.

.
.
.
.
.
.
.
.
.

.
.
.
.
.
.
.
.
.

.
.
.
.
.
.
.
.
.

.
.
.
.
.
.
.
.
.

.
.
.
.
.
.
.
.
.

2
8
12
16
21
25
29
32
36

f (x) dx, , -

- , x [a, b]. f (x), x, -


dx, x. - dx (
x) . , ""
, - , dx. , [a, b]
. ,
:
b
dx = b a

(1.1)
a

- ba
dx .
cdx, cdx ba
dx =
c(b a). :
b
(1.2)
c dx = c(b a)
a

, , :
b
(1.3)

b
cf (x) dx = c

b
(1.4)

f (x) dx

b
f (x) dx +

b
g(x) dx =

(f (x) + g(x)) dx
a

,
b
(1.5)

c
f (x) dx +

c
f (x) dx =

f (x) dx,
a

, ,
1 n
1
x dx. x dx. 0

1
2

x dx =

1
x dx +

x dx.
1
2

x x + 12

x dx -

1
2

(x+ 12 ) dx. ,
0

:
b
(1.6)

f (x) dx =
a

b+c
f (x c) dx,
a+c

. ,
- : f (x)dx x x + c ,
f (x)dx.
.
:
1

1
(1.7)

2
x dx =

1
(x + ) dx =
2

1
2

1
x+

1
2

1
x dx = +
2

1
2

1
x dx
1
2

1
(1.8)

2
x dx = 2

x dx +

1
2

, . x kx c
k. , y = kx
b
f (x) dx. x a b, y ka,
a

kb

kb

f (y) dy. , ,

ka

y x.
?
. dy dx. , k ,
k. - !
dx dy = kdx.
:
b
(1.9)

kb
f (x) dx = k

f (x/k) dx.
ka

-
! .
3

, 1
x dx. , y = 2x
0

2
x dx = 4

x dx.
0

(1.8) :

x dx

1
0

y = ax
xn dx.

b
a

f (x) dx =

x dx = 12 .

x dx. a

xn dx,

a
f (x) dx f (x) dx,

xn dx. -

f (x) dx ,

.
. ,
, .
:
b
(1.10)

f (x) g(x) x [a, b],

b
f (x) dx

f (x) dx
a


b
f (x) dx
a

.
[a, b] , a = x0 < x1 < < xn1 < xn = b,
[a, b]
b
f (t) dt =

n xk

f (t) dt

k=1x
k1


xk
f (t) dt (xk xk1 ) max f [xk1 , xk ]

(xk xk1 ) min f [xk1 , xk ]


xk1

:
n


(xk xk1 ) max f [xk1 , xk ]

k=1

(xk xk1 ) min f [xk1 , xk ]. -

k=1

|f (b)
f (a)| max(xk xk1 ).
,
.
.
: ,
- .
.
1. F (x, dx) G(x, dx)
, .
. , . , > 0
b
b
F (x, dx) G(x, dx) +
a

q F (x)
qG(x),
b

b
F (x) q

I(F ) =
a

G(x) = qI(G)
a

q < 1 + /I(G) .
. , |I(F ) I(G)| <
.
.
, - . , (??) xn ,
dxn = (x + dx)n xn = nxn1 dx + Cn2 xn2 (dx)2 + = nxn1 dx
,
.

.
. .
,
, .
.

, OPQ (O )
R = OP = OQ P Q,
.
ABC AB R
AC P Q. ABC OPQ. BC PQ
.
.
() ()
A (. O),
( ). () ABC, ()
OPQ.
, -
. .
, f (x) [a, b]
. dx , x. ds
f (x)dx, dx
f (x) (< df (x)dx).
,
b
f (x) dx
a

.
b
, xn dx y = xn
a
n+1

[a, b]. dx
n+1
xn dx dx ,
b n
b n+1
1
x dx n+1
dx
=
a
bn+1 an+1
.
n+1


.
. 6

. , x x(t).
t1
y(t) dx(t) t0

.
f (t) t df (t)
dt t.
dt , , .
b
df (x) = f (b) f (a)

(1.11)
a

.
, s(t), h.
b
s(h) dh , ,
a

a b. , ,
dh
h h-
.
.
1. .

2. |df (x)|.

3. g(x)df (x).

4. (g(x)df (x) f (x)dg(x).

. F (z) f (z)

f (z)dz.
b
f (z) dz a

F (b) F (a) .
, , ,
. , f (z)
, .

b
f (x) dx = F (b) F (a)

(2.1)
a

b < a.
b

a
f (x) dx =

(2.2)
a

f (x) dx,
b


.
:
b
(2.3)

c
f (t)dt +

c
f (t)dt =

f (t)dt
a

a, b, c.
.
2.1 ( ). [a, b] f (x)
, f ()(b a) S
f (x) [a, b].
. , f (x) > S/(b a),
f (x) S/(ba)(ba)
S, S, . , f (x) < S/(b a)
. , , .
.
1. (a, b) f (x) .

. f (x). x0 (a, b) . F (x) f (x) [x0 , x], x > x0


f (x) [x, x0 ],
x < x0 .
f (x) (a, b). x0 (a, b) F (x)
, f (x), x0 x, x > x0 ,
, x < x0 . , F (x) = f (x).
[x, x + n x], xn
, f (xn )
,
f (xn ) =

F (x + n x) F (x)
n x

n x , xn x. f (x)
f (x). , F (x) = f (x).
f (x) f + (x) =
1
(f
(x) + |f (x)|) f + (x) = 12 (f (x) + |f (x)|) . f (x)
2
, f (x).
F (x). F + (x) F (x)
f (x).
.
. , [x]
. , -
, ,
- .
, , , . ,
. -
[a, b] x1 , . . . , xn ,
. x0 = a xn+1 = b.
(xk , xk+1 ) Fk (x) + ck
ck ,
{Fk (x) + ck } ,
.
. f (x) ,
b
F (x). f (x) dx a

(b) = F (b) F (a), ,


, , (b) = F (b) = f (b).

2 ( ). : [t0 , t1 ] [0 , 1 ]
(t0 ) = 0 (t1 ) = 1 f (t) f ( (t)) (t)
[t0 , t1 ].
t1
(2.4)

f ( (t)) (t) dt =
t0

f ( ) d,
0

. F ( ) = f ( ), F ( (t)) f ( (t)) (t). (2.4) F (1 ) F (0 ),


F ( (t1 )) F ( (t0 )),
.
b
(2.5)

b
cf (x) dx = c

b
(2.6)

f (x) dx

b
(f1 (t) + f2 (t)) dt =

b
f1 (t) t +

f2 (t) dt
a

F (t) = f (t), (cF (t)) = cf (t), .


Fi (t) = fi (t), (F1 (t) + F2 (t)) = f1 (t) + f2 (t),
.
t [a, b] f1 (t) f2 (t), .
b

b
f1 (t) dt

(2.7)
a

f2 (t) dt
a


. b = a .
, f1 (b) , f2 (b),
b > a, (2.7)
.
. f (x) x - n 0, dx x, df (x)
10

{f (x + n ) f (x)}, dx f (x).
df (x) = f (x+dx)f (x)
df (x) = f (x)dx,

(2.8)


f (t)dg(t) f (t)g (t)dt.
3 ( .). f (x)
g(x) -,
b

b
f (t) dg(t) = f (b)g(b) f (a)g(a)

(2.9)
a

g(t) df (t)
a

. , f (x)g(x) f (x)g (x) . a


b. f (b)g (b),
(f (b)g(b) + f (b)g (b)) g(b)f (a). . b = a
.

.
1.
2.
3.
4.
5.
6.
7.
8.
9.
10.
11.

dx
x2 x

xex dx
2

x5 e2x dx
x cos xdx
x3 ln xdx
ex sin xdx
ln xdx
arctg xdx
sin4 xdx
dx
1+x3

(1

)
sin kt
t

dt
k

11

. , x! x.
- (x), x -, :
(3.1)

(x + 1) = x(x)

(1) = 1, ,
n (n) = (n 1)!.
, - :
(3.2)

nx n!
n x(x + 1) . . . (x + n)

(x) = lim

. (x) = ln (x) (
-):
(x) = ln x.
.
, ,
.
f ,
x < y < z :
(3.3)

f (z) f (y)
f (y) f (x)

yx
zy

ax + b, a.
3.1. ( ) .
. [a, b] .
3.2. f (x)
x a

f (a)f (x)
ax

. x > y > a, f (x)


yx
.
f (y) f (x) (f (x) f (a)) xa
f (x) f (a),
(
)
yx
ya
f (y) f (a) (f (x) f (a)) 1 +
= (f (x) f (a))
,
xa
xa
y a .
12

.
3.3. f (x) 0 [a, b],
f (a) f (b)
f (a)
f (b)
ab
. f (x) 0, f (x) . g(x) = (f (x)f (a))f (a)(x
a). f (x) f (a) . , g(x)
g(b) g(a) = 0. .
.
3.4. f (x) [a, b],

f (a) f (b)
f (a)
f (b)
ab
. f (b) = lim

xn = b n1 ,

f (b)f (xn )
,
bxn
f (b)f (xn )
bxn

(b)
f (a)f
3.2,
ab
. .

1. f (x),
[a, b], , f (x) 0
x .
. f (t) 0. x <
y < z . 3.3
f (y) f (x)
f (z) f (y)
f (y)
,
yx
zy
f (t).
f (t) , x < y 3.4

f (y) f (x)
f (x)
f (y),
yx
, f (t) . , , , .
x12 ,
ln(x + a)
a.

13

-.
2. (x), ln x 0,

(x) = lim ln
n

nx n!
x(x + 1) . . . (x + n)

. nx n!

. ln x(x+1)...(x+n)
ln nx n! = x ln n + ln n! ln(x + k).
f (x) .
x (0, 1) n. f (1) = 0,
f (n) = ln(n 1)!. f
f (x + n) f (n)
f (1 + n) f (n)
f (1 + n) f (n)

1 + n n
x+nn
1+nn
, f (n) = ln(n 1)!,
ln(n 1)

f (x + n) f (n)
ln n
x+nn

f (x + n)
ln ((n 1)x (n 1)!) f (x + n) ln (nx (n 1)!)
n

f (x + n) = f (x)x(x + 1) . . . (x + n 1) = f (x)x
f (x)
n

ln ((n 1)x (n 1)!) ln x f (x + n) ln (nx (n 1)!) ln x

n
n n + 1.
ln (nx n!) ln x

n+1

f (x) ln (nx (n 1)!) ln x

ln(x+
n) ln n = ln(1 + nx ). , .
(x) . , f (x) = (x) x, (0, 1), x.

3 (). , x > 0, (x + 1) = x(x)
1.

14

(
) (x)

=) ( x+1
2 ) 2 . G(x+
) ( x+1 ) .
) G(x)
( x+2
(x
) ( x+1
(
1) = 2 2 = 2 + 1 2 = x2 x2 x+1
= x2 G(x). 2
G(x)2x -.
G(x) , , , G(x)/G(1)
x
, G(x)2
G(1)21 = (x). x 2x
(3.4)

22x1 (x + 0.5)(x)
(0.5)

(2x) =

.
1. .
2. (0) (1)?
3. lim (x n)(x n)
x0

4.

1
p

1
q

= 1 xy

5. ,

k=1

k
x+k

( k+1 )x
k

k1

6. , x = kx

xp
p

yq
q

= (x + 1)
k

k, x =

(x+1)
(xk+1)

7. , x

k+m

= x (x k) .

8. ,
.

1
x2

9. ,

1
x

10. . ln x .
11. , .
12. ,
.
13. xx 2 ex e(x)
)(x),
(
( ) (x)
(x) = 1 x + 21 ln 1 + x1
1

15


-:
1 (Euler). x 0 (x) =

tx1 et dt

. x = 1 et dt = et |0 = 1.

x t

t e

dt =

0
x

t de

= tx et |0 +

et xtx1 dx

, . .
. x < y < z =
f (z)f (y)
zy
yx

zx . 1 = zx .
zy
f (y)f (x)
yx

y x = (1 )(z x) z y = (z x)
(1 )(f (z) f (y)) (f (y) f (x)). ,
, y = x+(1)z ,
:
(4.1)

f (x + (1 )z) f (x) + (1 )f (z),


.

2.
.
. f (x) g(x)
(4.2)

f (x + (1 )y) f (x) f (y)1

g(x + (1 )y) g(x) g(y)1


(4.3)

f (x + (1 )y) + g(x + (1 )y) (f (x) + g(x)) (f (y) + g(y))1

,

(4.4)

f (x)f (y)1 + g(x) g(y)1 (f (x) + g(x)) (f (y) + g(y))1

, 4.1.
4.1. a, b, c, d, < 1

a b1 + c d1 (a + c) (b + d)1
16

a
b
. x = a+c
, y = b+d
,
(a + c)(b + d)

x y 1 + (1 x) (1 y)1 1

(4.5)

y
x.
)
(
( y )1 ( 1 y )1

x1 y 1 (1 x)1 (1 y)1 =
x
1x
, x < y , x > y
. ,
x = y. .
4.2. .
. .
4.3. f (x, t) t t
b
[a, b]. f (x, t) dt
a

x.

f (x, tk )(tk tk1 ), t0 = a < t1 <

k=1

< tn = b . [a, b] fn (x, t), (tk1 , tk ) f (x, tk ). ft (x, t) M ,


[tk1 , tk ] , |fn (x, t) f (x, t)|
[a, b] M . , b
b
f (x, t) dt fn (x, t) dt (b a)M a

.
n


f (x, tk )(tk tk1 )

k=1

f (x, t) dt,

.
1. n
lim et tx1 dt n 0

. n
. et tx1 dt
0

4.3.

17

-. - B(x, y),
x, y > 0

1
(4.6)
B(x, y) =
tx1 (1 t)y1 dt.
0

, x, y > 0.

1/2

tx1 (1 t)y1 dt,

tx1 (1 t)y1 dt.

1/2

0,
[
]
[
]
0, 12 21 , 1 (t) (t) , 1/2
1
0 (t)dt 1/2 (t)dt. 0 t 1,
(1 t) t . y1
tx1
,
[ (1
] t)
1
[.

0,
,

2
]
1
(1 t)y1 1t
12 , 12 , 1 tx1 1t 2.
t

1/2
0

x1

(1 t)

2tx1 dt

y1

1
1/2

{
[
]
2tx1 t 0, 12
[
]

2ty1 t 12 , 1
2(1 t)y1 dt .

4.4. x, y
(4.7)

B(x, y) = B(x + 1, y) + B(x, y + 1),

. 1 = t + (1 t),
tx1 (1 t)y1 = tx (1 t)y1 + tx1 (1 t)y ,
t (4.7).
4.5. x, y
(4.8)

B(x + 1, y) =

x
B(x, y + 1).
y

.
(
)
1
1
(1 t)y
x
y1
x
B(x + 1, y) =
t (1 t)
dt =
t d
=
y
0
0
1


1 x
1 1
x 1 x1
x
y
y x
= t (1 t) +
(1 t) dt =
t
(1 t)y dt = B(x, y + 1).
y
y 0
y 0
y
0

18

(4.7) (4.8) ,
(4.9)

x
B(x, y)
x+y

B(x + 1, y) =

( B(x, y + 1) (4.7) B(x + 1, y), (4.8)).


x + y (4.9) -. , B(x, y)
(x + y), x + y
x ( , x + y) 1.
f (x) = B(x, y)(x + y) ( y ,
y ). -.
x : x 7 (x + y) x 7 B(x, y).
-. , f (x) (x)
a. f y, (
) y. ,
(4.10)

B(x, y)(x + y) = a(y)(x)

a(y), x = 1. , (1 + y) = y(y)
(1) = 1; , B(1, y). :

B(1, y) =

11

(1 t)

y1

dt =

1
(1 t)y
1
d (1 t)y
dt =
= y.
dt
y
y
0

, y1 y(y) = a(y)1, .. a(y) = (y). ,


(4.11)

B(x, y) =

(x)(y)
(x + y)

4.11 (1/2):
(

/2

d sin2

=
x(1 x)
0
0
sin2 cos2
/2
/2
2 sin cos d
=
2d = .
sin cos
0
0
( )
(
)
(4.11) , 2 21 = B 12 , 12 (1).
( )

= .
(4.12)
2
B

1 1
,
2 2

ds

.
1. (0) (1)?
19

2. lim (x n)(x n)
x0

3.

1
p

1
q

= 1
xy

4. (x) =

1 (
0

5. (x) =

ln 1t
1

et x

6. (1 + x1 ) =
7. B(x, y) =

x1

1
x

)
dt

dt

et dt
x

8.

tx1
(1+t)x+y

dt

xp (1 x2 )q dx

9.

/2

cos x sin x dx

10.

11.

tx
1+t

sin x

dt =

/2

(tg )2x1 d =

12.

eat tx1 dt =

(x)
ax

1 (

13. (x) =

14. (x) =

ln 1t
1

et x

15. (1 + x1 ) =
16.

1
0

17.

1
0

18.

1
0

sin x

x1

1
x

dt

dt

et dt
x

( m
n )

m1
t
1tn

dt =

1
1t4

dt =

2 ( 14 )

32

1
1t3

dt =

3 ( 1 )
3
3 3 16

1
n( m
n +2)

20

xp
yq
+
p
q

.
f (x) F (x) F = f . f = 0 1 .
1-
.
F (x) =

(5.1)

f (x + k)

k=0

. (5.1) f (x) =
n > 1. ,
(5.2)

=(x)

k=1

1
xm

m 2 x = n

1
(x + k)2

(1+x)
2 . =(0)
.

1. f (x) f (x) =
1
(1+x)

.
2 , f (x) =(x)
. - , f (n)
=(n) . lim =(x)

= 0, lim f (n) = c.
x

f lim f (x) = c.
x

lim f (x)
=(x) = c.
x
x .
1
(1+x)
2
x .
.

1
x+k ,

x1 , .
k=0
)
(

1
1
1

x+k k [k = 0] , x ,
k=0

. ,
(5.3)
)
)
(

1
1
1
1
1
1
[k = 0] +
[k = 0] =

= .

x+1+k k
x+k k
x+k
x
k=0

k=0

k=0

(5.4)

-(x) = +

1
k=1

1
x+k

. . - 1 .

1+x
21

2. ,
1
(1+x) (x) .
. f (x) , 1
1+x
. [0, 1] n 1
f (x) |f (n+)f (n)| |f (n+1)f (n)| = n+1
.
1
-(n + )
-(n)| n+1 . g(x) = f (x)
-(x)
|

(5.5)

-(n + )
-(n)| =
|g(n + ) g(n)| |f (n + ) f (n)| + |

2
.
n+1

g(x) , , 1-
. (5.5) n . n
-(x).
g(n+) = g(n) = g(1) , f (x)
- = =.
5.1.

- (x) = =(x),

F (x) =
. ,
x

=(t)
dt. F (x) = =(x)

0.
1

1
1
(F ) = F =
=(x) = (1+x)
2 . F = 1+x + c, c -(x). ,
. 2 F (x + 1) cx =
-(x) = F (x + 1) + c = =(x).
-

,
1
1
- (x) = (1+x)
-(x) = 1+x

.
2.

, (x) = =(x)

1.

ln k.
ln(x + k).

k=0

ln x

(ln(x + k) ln k) = ln x

k=1

k=1

k=1

ln(1 +

x
k ).

ln(1 + x) x, .
xk k- . .

F (x) = ln x
(ln(1 + xk ) xk ). n-
k=1

( (
)
) ( (
x+1
x+1
x) x)
ln 1 +

ln 1 +

=
k
k
k
k
(
) (
x+1
x)
1
ln(x + k + 1) ln k
ln(x + k) ln k
= ln(x + k)
k
k
k

22

,
(5.6) F (x) = ln x
(

k=1

ln(x + k)

1
k

)
=

))
1
lim ln x
ln(x + k)
=
n
k
k=1
)
(
n

1
=
lim ln x ln(n + x) +
n
k
k=1
)
( n
1
ln x + lim (ln(n) ln(n + x)) + lim
ln n = ln x +
n
n
k
n (

k=1

:
(x) = x ln x

(5.7)

( (

x) x)
ln 1 +

k
k

k=1

3. (5.7) x
. (x),
(1) = 0 (x) = ln x.
.

x
1+x

ln(1 + x) x


2
x
x
.
| ln(1 + x) x|
x =
1+x
1 + x

(5.8)

x .

((
)
)

ln 1 + ky ky (5.8),

lim

k=1
n

n k=1

k=1

x2
k2 .

(5.7).

(ln(1+ k1 ) k1 ) = lim (ln n


n

k=1

1
k)

= , (1) = 0.

. (x) exp((x))
, (x) , . (5.7)
:
(5.9)

(x) =

ex (
x )1 x
ek
1+
x
k
k=1

.
(5.10)

{(

x) x }
ex
1
en =
n
x(x)
n=1

23

{(

x) x }
ex
1+
e n =
n
x(x)
n=1

, ,
)
(

2
(5.10). ,
1 nx2 2 .

n=1

(1

k=1

x 1
(1
n )

x 1
.
n )

e n e n ,
x

{(

(5.11)

n=1

x ) x }1 {(
x ) x }1
n
e
e n
1
1+
n
n
n=1

(5.10) x x. (5.11)
x (x/)ex/ , x (x/pi)ex/ .
(1 x/) = x (x/),
)
(

x2
x
x
x
1 2 2 = (x/)ex/ (x/pi)ex/ = (1 x/) (x/pi)
n

n=1
x/
, , sinx/
, x x
-:

(x)(1 x) =

(5.12)

sin x

.
1.

n=1

2.

n=1

1+

1
n2

1+

x
n

)(

1+

2x
n

)(

3. - .
)
(
1 + n14
4.
)
(
5.
1 + n13
)
(

2
1 nx2 2
6.
n=1

7.

1
0

ln (x)dx = ln 2.

24

3x
n

dx
x . .
, .
.
b
(6.1)

b
f (t) dt =

b
Re f (t) dt + i

Im f (t) dt
a

f (z) g(z) . , , b
f (z) dg(z) a

. , p : I C.
f (z) dg(z)

p f (z) dg(z)
p

(6.2)

b
f (z) dg(z) =

f (p(t))g (p(t))p (t) dt

.
.
p1 : [a, b] C p2 : [a , b ] C ,

p1
2 p1 : [a, b] [a , b ] p1 (t) =
p2 ( (t)). ,

b
f (z) dg(z) =

p1

f (p1 (t))g

(p1 (t))p1 (t) dt

b
=

f (p2 ( (t)))g (p2 ( (t)))(p2 ( (t))) dt

,
,
. (t)

b

f (p2 ( ))g (p2 ( ))(p2 ( )) d =


a

f (z) dg(z)
p2

25

, (a) = b
(b) = a . .

, .
-
1. - f (z), p(t) : [a, b] C

(6.3)
f (z) dz = f (p(b)) f (p(a))
p

f (z) dz =
p

f (z(t)) dz(t) =
a

f (z(t))z (t) dt =
a

b
=

f (z(t)) dt =

Re f (z(t)) dt + i

Im f (z(t)) dt =

= Re f (p(b)) Re f (p(a)) + i(Im f (p(b)) Im f (p(a))) = f (p(b)) f (p(a)).

(z n ) = nz n1 ,
n+1
z n dz = zn+1 .
dz
z . p(t) = r(t)eit , t [0, T ], c
p(0) = 1 p(T ) = Z.

(6.4)
p

dz
=
z

T
0

dr(t)eit
=
r(t)eit

e it dr(t)
+i
r(t)eit

T
dt = ln |Z| + i arg Z
0

dz
z i. , , 2i. ,
,
H
: . ,
:
I
(6.5)

dz
= 2i
z

,
.

26

. p(t) ,
z0 .
I
1
dz
(6.6)
2i
z0 z
p

p(t) z0 , .
6.1. .
. , (??) p(t) z0 = r(t)ei(t) , t [0, l], r(t) = |p(t) z0 | p(l) = p(0).
I
(6.7)
p

dz
=
z0 z

r (t)ei(t) + ir(t)ei(t) (t)


dt =
r(t)ei(t)

l
i d(t) = ln r(l) ln r(0) + i((l) (0))

d ln r(t) +
0

r(0)ei(0) = r(l)ei(l) , (l) (0) = 2k k.


.

, . ,
, . , , , , c ,
,
.
1.
2. , ,

3.
.
dz
6.2.
z0 z z0 p(t)

.
. dz
z0 ,
z0 z z0 ,
p(t)

. z0
. , .
27

, z0 . z0
.
2. D ,
H
D . D z0dz
z
z0 D 2i
D.
. z1
D, z D z z1 c . z1dz
z D
,
. z1 D . z2 D c z1
z(t). D z(t) t
, , . ,
D.
D.
D. , D [1, 1]
(0, 1], .

/ D D .
p1 (t) (, )
D, D
[1, 1] p2 (t) p1 (t)
D
. A B p1 (t) p2 (t). p1 (t)
z0 = , z0 p1 (t) .
arg(B + ) arg(A + ) arg(B) arg(A).
z0 = , z(t) = p2 (t) z0
z0 p2 (t) = r(t)earg(z0 p2 (t)) . ,
( arg(B ))( arg(A))
0 2 + arg(A) arg(B). p1 2,
p2 6.2.
2. 2,
2.

28



(7.1)
|f (t)|dt f (t)dt

.
, .
ei ,
.
. p : [a, b] C
b
|p (t)| dt. -
a

. , t( ) : [c, d] [a, b] t ( ) ,
d

|p (t( )| dt( ) =
c

|p (t( ))|t ( ) d =
c

|p (t( ))t ( )| d =
c

|p (t( ))| d

p(t) = a + t(b a) , |p (t)| = |b a|

| dz| =

|b a| dt = |b a|,

.
p(t) = c+re t [, ], |p (t)| =
r r( ), .

.
7.1 ( ). p(t) L
f (z), |f (z)| C
z p, :






f (z) dz LC




p

f (z) dz =

f (p(t)) dp(t) =

b
a

f (p(t))p (t) dt


b


b
b


f (p(t))p (t) dt |f (p(t))p (t)| dt C|p (t)| dt = LC




a

29


7.2 ( ). f (z) , ABC,
B

C
dz +

C
f (z) dz =

f (z) dz
A

f (z) dz -

ABC

ABC. A , B , C
ABC.
.
.
I
I
I
I
I
f (z) dz
f (z) dz +
f (z) dz +
f (z) dz +
f (z) dz =
ABC

AC B

BA C

, |

CB A

A B C

f (z) dz| I,

ABC

I1 , I/4. "" , ,
.
I/16. An Bn Cn
1/2n In I/4n . P , n-
Pn = P/2n . z0 . f (z) z0
f (z0 +z) = f (z0 )+f (z0 )z +o(1)z.
,
f (z) An Bn Cn o(1)z
o(1)Pn2 ,
.
7.3. f (z), D , ( ),
.
.
. . . , ,
.
1 (). f (z)
D , D.
30

. -, z
f ()d z0 z .
z0

. ,

D . D. ,
, D , D. D
( D0 :
D .) , D .
, D : D .
, D D 7.3.
z1 .
z
z1
z
f ()d = f ()d + f ()d, z0

z0

z1

, F (z) =

f ()d

z0

, . ,
f (z). , z+z

F (z)
f ()d. f () =
z

f (z) + o(1) z 0,
f (z) + o(1).
2 (). f (z) -
H
D , f (z)dz = 0
, .
. - ,
.
- ,
-.

.
1.

H4
0

2.

dz
(z1)(z2)(z3)

3.

H1
1

4.

dz
z 4 +1

d
5+3 cos

cos2 d
13+12 cos

31

8.1. f (z) - D
z1 , . . . , zn ,

I

n I

f (z)dz =

f (z)dz

k=1 z

. ,
zk Dk zk D
.
D D Dk .
D .
n H
H


f (z)dz
f (z)dz
D

k=1 zk


.
1 ( ). f (z) -
D ,
I
D

f (z)
dz = 2if (z0 )
z z0

. 8.1
z0 .
,
I
f (z)
lim
= 2if (z0 ).
0 |zz |= z z0
0
H
1
|zz0 |= zz
= 2i, 0

I
f (z) f (z0 )
lim
= 0,
0 |zz |=
z z0
0
. , f (z) z0 , .
. z0
f (z), f (z)
f (z), .
f (z) z0
( resz=z0 f (z))
(8.1)

1
resz=z0 f (z) =
2i

I
f (z)dz,
z0

32

, - z0
z0 .
2 ( ). f (z)
D ,
I

f (z)dz = 2i
resz f
zD

. z1 , . . . , zn f (z) D. zk Dk zk
rk , D. , D
Dk .
f (z) , f (z) , .
, sinz z , z.
8.2. f (z) C, ,
-
H f ()d
(z)
2
.
(I
)
I
I
1
f ()d
f ()d
f ()d
(8.2) lim

= lim
z0 z
z0
z z
z
( z z)( z)

z 0
I
I
I
f ()d
f ()d
zf ()d
(8.3)

=
,
( z z)( z)
( z)2
( z z)( z)2
M |z|L,
M f (z) L
, , .
3 ( ). f (z) -
z0 lim (z z0 )f (z) = 0, zz0

lim f (z) , f (z) z0 ,


zz0

- z0 .
. lim (z z0 )f (z) = 0 zzH
0
z0 , f (z)dz
f (z)
0 lim (z z0 )f (z) = 0
zz0

33

0 < |z z0 | <
I
2if (z) =
z0

f ()d
z

,
|zz0 | < R, f (z) z0
.
.
4. - f (z) f (z)
z0 z0 , zz
0
.
. k lim (z z0 )k f (z), z0 f (z)
zz0

k .
8.3. f (z) n z0 , n

ak
f (z) = g(z) +
, g(z) z0 .
(zz0 )k
k=1

. k ,
lim f (z)(z z0 )k , z0 k 1. zz0

, f (z)(zz0 )k1 lim f (z)(z


zz0

z0 )k1 , k.
5. k
(8.4)

res f (z0 ) = (k 1)! lim (f (z)(z z0 )k )(k1)


zz0

.
f (z) =

ak
ak+1
a1
+
+ +
+ f0 (z),
k
k1
(z z0 )
(z z0 )
(z z0 )

f0 (z) z0 . (z z0 )k ,
k 1
z z0 , (k 1)!a1 .
, (8.4).
.

(8.5)

res f (z0 ) = lim f (z)(z z0 )


zz0

34

, f (z)
z0 k, f (z0 ) = f (z0 ) = f (z0 ) = = f (k1) (z0 ) = 0
f (k) (z0 ) = 0.
.
8.4. P (z)/Q(z) z0 z0 k,
.
. P (z) n, z0
an (z z0 )n . Q(z) bn+k (z z0 )n+k .
lim P (z)(z z0 )k /Q(z) = an /bn+k .
zz0

6 ( ). f (z) g(z) f (z0 ) = g(z0 ) = 0

(z)
(z)
lim fg (z)
. lim fg(z)

zz0
zz0

lim

zz0

f (z)
f (z)
= lim
g(z) zz0 g (z)

. f (z) = am (z z0 )m + . . . g(z) = bn (z z0 )n + . . . .
f (z) = mam (z z0 )m1 + . . . g (z) = nan (z z0 )n1 + . . . .
m > n, . m < n,
. m = n,
.

.
1.

1
z+z 3

2.

1
(z 2 +1)2

3. ctg z
4.

1
ez +1

5.

1
sin z 2

6.

1
z2

ctg z

7. ctg2 z

35

- .

?
.
. ,
. .
, . . ,
, , .

.
( ) .
, . . -, , ,
0/0, . , , , ,
. .
. , , ,
.
- . ,
.
, , - . ,
. - , 2
1
, . , xx1
x + 1
- ,
, x = 1
, , .
, , . ( ,
, .)
,
. , , ,
, . , , .
,
, .
36

, ,
. , , . , , , - . - .

1.

fk (z) -

k=1

|fk (z)| ck D, p(t) D



(9.1)

fk (z)dz =

p k=1

k=1

fk (z)dz
p

.
(9.2)

fk (z)dz =

p k=1

k=1

fk (z)dz
p

n (9.1). (9.1).


fk (z)dz. p
k=n+1

Cn =

ck ,

k=n+1

. Cn , ,
, n.
.
2. f (z) |z z0 |
R, |z z0 | < R
(9.3)

f (z) =

k=0

I
(z z0 )k
|zz0 |R

f ()
d,
( z0 )k+1

|z z0 | < R.
. z |z z0 | < R
. | z0 | > |z z0 |

(9.4)

(z z0 )k
1
1
1
1
=
=
=
0
z
( z0 ) (z z0 )
z0 1 zz
( z0 )k+1
z0
k=0

37

| z0 | = R

|zz0 |k

r > |z z0 |. f () | z0 | = R
Rk+1
k=0

( ). (9.4) f ()
.
I
(9.5)

f (z) =
|zz0 |R

k=0

|zz0 |R

f ()
(z z0 )k
d =
z

f () d
( z0 )k+1

ak xk

k=0

x, x > 0.
ak (z z0 )k
k=0

R, ,

|ak ||z z0 |k < |z z0 | < R


|ak ||z z0 |k = |z z0 | > R.
k=0

k=0

z0 R .
z . .
,
. : ,
.
.
, , ,
. , , , ,
.
, , arctg x 5, 1 i.
, x21+1 i.
,
i, 1, 5 .

3. f (z) D
1. D
2. D
3. , D
38

. , .
. - ( ).
,
. , -,
. .
.
4 (). , , ,
, .
. z0 zk , A(z) B(z).

ak (z z0 )k , an = 0
A(z) B(z)
k=n

. z z0

ak (z z0 )kn |an |/2.


k=n+1

ak (z z0 )k = (z z0 )n ak (z z0 )kn = 0

k=n

, z0 . ,
.
z0 .
D0 , A(z) B(z)
. D0 D,
z1 D0 D. D0 , . ,
z1 . , z1 D0
. D0
.
, 2, .

(9.6)

f (n) (z) =

n!
2i

IR
z0

39

f ()
d
( z0 )k+1

.
1.

H2
0

2.

H2
0

3.

4.

5.

6.

dx

cos x
(x2 +1)

dx

1
(1+x2 )2

dx

7.

ez dz
(z 2 +1)2

1
1+x4

1
0

ez dz
z 3 (z+1) .

(1+x2 ) cos x
1+x4

ln(1x)
x

dx

dx

40